Pengkayaan Protein Mie Instant dengan Tepung Tahu - Yustinus Marsono; W. Pandhu Astana (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2002)
A study on fortification of tofu flour in instant noodle has been conducted. The objective of this study is to determine the effect of tofu flour addition on chemical, nutritional and physical properties as well as panelist acceptance of the instant noodles. Four level of tofu flour fortification were evaluated, i.e. 10%, 12%, 14% and 16% wheat flour by weight. It is found that fortification of 16% tofu flour increased protein content instant noodles to 18% (from 9%) but decreased the in vitro protein digestibility from 58.7% to 46.8%. The energy content increased from 451 Kcal to 461 Kcal per 100 g of instant noodles. Fat content increased by 1.6% but carbohydrates decreased by 10.6%. Elasticity and deformation tend to decrease with increasing addition of tofu flour, but no significant effect is shown on the ectensibility of instant noodles. Rehydration capacity decreased by 5.5% and cooking loss increased to 3.25% on the noodle added with 16% tofu compared to 1.96% in the control noodle. Expansion of noodles are increased with the addition of tofu flour but are similar for the difference level of tofu flour added. Among the level of tofu flour added, addition of 12% resulted in the most preferable noodle.